Evaluation of the analgesic effect of oral sucrose solution on neonates undergoing a minor painful procedure - Kallol Paul; Pankaj Kumar Halder; Rituparna Das; Arpita Choudhury; Prerna Goenka; Sourav Roy (Wolters Kluwer Medknow Publications, 2022)
Background: Pacifying newborns by nonpharmacological methods during painful procedures is a frequent and difficult problem in routine practice. Purpose: The purpose of the study was to determine the analgesic effects of oral sucrose solution in comparison to placebo (sterile water) in neonates. Materials and Methods: A prospective, double-blinded study of 100 neonates who were divided into two groups after simple randomization, to give either 30% sucrose solution (group A) or sterile water (group B) during an intravenous catheterization. Assessment of pain by the Douleur Aigue Nouveau-ne scale (DAN) and changes in the heart rate (HR), respiratory rate (RR), or arterial oxygen saturation (SpO2) during peripheral vein catheterization were analyzed. Results: The mean change of HR, RR, and SpO2 was more in group B compared to group A. The mean DAN scores were 2.24 ± 2.026 and 6.92 ± 2.538 in group A and group B, respectively. None of these results were statistically significant (P > 0.05). Conclusion: There was a less prominent change in HR, RR, and SpO2 with response to noxious stimuli with oral sucrose administration in newborns when compared to placebo.